Novel role of NPY in neuroimmune interaction and lung growth after intrauterine growth restriction - Thangaratnarajah, Chansutha; Dinger, Katharina; Vohlen, Christina; Klaudt, Christian; Nawabi, Jawed; Garcia, Eva Lopez; Kwapiszewska, Grazyna; Dobner, Julia; Nuesken, Kai D.; Van Koningsbruggen-Rietschel, Silke; von Hörsten, Stephan; Doetsch, Joerg; et al. (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2017)
Individuals with intrauterine growth restriction (IUGR) are at risk for chronic lung disease. Using a rat model, we showed in our previous studies that altered lung structure is related to IL-6/STAT3 signaling. As neuropeptide Y (NPY), a coneurotransmitter of the sympathetic nervous system, regulates proliferation and immune response, we hypothesized that dysregulated NPY after IUGR is linked to IL-6, impaired myofibroblast function, and alveolar growth. IUGR was induced in rats by isocaloric low-protein diet; lungs were analyzed on embryonic day (E) 21, postnatal day (P) 3, P12, and P23. Finally, primary neonatal lung myofibroblasts (pnF) and murine embryonic fibroblasts (MEF) were used to assess proliferation, apoptosis, migration, and IL-6 expression. At E21, NPY and IL-6 expression was decreased, and AKT/PKC and STAT3/AMPKα signaling was reduced. Early reduction of NPY/IL-6 was associated with increased chord length in lungs after IUGR at P3, indicating reduced alveolar formation. At P23, however, IUGR rats exhibited a catch-up of body weight and alveolar growth coupled with more proliferating myofibroblasts. These structural findings after IUGR were linked to activated NPY/PKC, IL-6/AMPKα signaling. Complementary, IUGR-pnF showed increased survival, impaired migration, and reduced IL-6 compared with control-pnF (Co-pnF). In contrast, NPY induced proliferation, migration, and increased IL-6 synthesis in fibroblasts. Additionally, NPY-/-mice showed reduced IL-6 signaling and less proliferation of lung fibroblasts. Our study presents a novel role of NPY during alveolarization: NPY regulates1) IL-6 and lung STAT3/AMPKα signaling, and2) proliferation and migration of myofibroblasts. These new insights in pulmonary neuroimmune interaction offer potential strategies to enable lung growth.
EVALuna2:32789